Manifesta 13 Marseille : Final Report Booklet 2- Le Tiers Programme: The Education & Mediation Programme (Manifesta Foundation, Amsterdam, 2020)
Manifesta, the European Nomadic Biennial, takes place every two years in a different European city. The biennial rethinks the relationships between culture, society and urbanism, investigating and catalysing positive social change through contemporary culture in continuous dialogue with its host city and its citizens.
English
Keywords: N4390-5098 Visual Arts. Exhibitions